2024
DOI: 10.1186/s12951-024-02475-8
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in enhances peripheral nerve orientation: the synergy of micro or nano patterns with therapeutic tactics

Majid Sharifi,
Mohammad Kamalabadi-Farahani,
Majid Salehi
et al.

Abstract: Several studies suggest that topographical patterns influence nerve cell fate. Efforts have been made to improve nerve cell functionality through this approach, focusing on therapeutic strategies that enhance nerve cell function and support structures. However, inadequate nerve cell orientation can impede long-term efficiency, affecting nerve tissue repair. Therefore, enhancing neurites/axons directional growth and cell orientation is crucial for better therapeutic outcomes, reducing nerve coiling, and ensurin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 123 publications
0
0
0
Order By: Relevance
“…In essence, M1 macrophages kickstart the healing process in the initial three to 5 days by clearing debris and pathogenic contamination through phagocytosis and secreting TNFα, IL-1α and IL-1β and metalloproteinase ( Liu et al, 2019 ). Subsequently, the transition of M1 macrophages to M2 macrophages and the release of anti-inflammatory cytokines like IL-4/IL-13 and IL-10 promote activities such as proliferation, maturation, migration, resolution of inflammation, and angiogenesis ( Boukelmoune et al, 2021 ; Sharifi et al, 2024 ).…”
Section: Strategies For Msc-based Pn Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…In essence, M1 macrophages kickstart the healing process in the initial three to 5 days by clearing debris and pathogenic contamination through phagocytosis and secreting TNFα, IL-1α and IL-1β and metalloproteinase ( Liu et al, 2019 ). Subsequently, the transition of M1 macrophages to M2 macrophages and the release of anti-inflammatory cytokines like IL-4/IL-13 and IL-10 promote activities such as proliferation, maturation, migration, resolution of inflammation, and angiogenesis ( Boukelmoune et al, 2021 ; Sharifi et al, 2024 ).…”
Section: Strategies For Msc-based Pn Regenerationmentioning
confidence: 99%
“…Studies have shown promising results using MSCs to regenerate peripheral nerves in synergy with therapeutic techniques such as drug therapy, cell therapy, and electrical stimulation ( Zuo et al, 2020 ; Supra et al, 2023 ; Sharifi et al, 2024 ). However, technical challenges make it difficult to implement synergistic approaches.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…It is imperative to develop new feasible nerve grafts as alternatives for the treatment of PNI. With the development of material science and tissue engineering, numerous artificial nerve grafts made by various synthetic and natural biomaterials have been devised [ [8] , [9] , [10] ]. Because of their low cell affinity and poor hydrophilicity, synthetic biomaterials are difficult to obtain neurotherapeutic functions comparable to natural biomaterials, and have therefore been gradually replaced by the latter [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%